Answer:
12?
Step-by-step explanation:
i might be wrong, but from what it looks like, it shows 3 sections and one is labeled 4.
Let,
digital cameras be "x"
video cameras be "y"
Now,
According to the question,
5x + 3y = $3,213..................................................equation (1)
y = 4x..................................................................equation (2)
Taking equation (1)
5x + 3y = $3,213
Substituting the value of "y" from equation (2), we get,
5x + 3(4x) = $3,213
5x + 12x = $3,213
17x = $3,213
x = $3,213 / 17
x = $189
Taking equation (2)
y = 4x
Substituting the value of "x", we get,
y = 4 ($189)
y = $756
Now,
John buys a digital and a video camera. So, it costs him ($189 + $756) = $945
Answer:
c. (x + 3)
Step-by-step explanation:
using factor theorem
if x - 3 is a factor then p(a) = 0
p(a)= x^3 - 3x^2 - 4x + 12
a.(x-3)
p(3) = (3)^3 - 3(3)^2 - 4(3) + 12
= 27 - 27 - 12 + 12
= 0
therefore x-3 is a factor
b.(x + 2)
p(-2) = (-2)^3 - 3(-2)^2 - 4(-2) + 12
= -8 -12 + 8 + 12
,= 0
therefore x + 2 is a factor
c.(x + 3)
p(-3) = (-3)^3 - 3(-3)^2 - 4(-3) + 12
= -27 -27 + 12 + 12
= -30
therefore x + 3 is not a factor
d.(x-2)
p(2) = (2)^3 - 3(2)^2 - 4(2) + 12
= 8 -12 - 8 + 12
= 0
therefore x - 2 is a factor
Answer:
Radius
Step-by-step explanation: